The grief experiences of the Adult Intensive Care Unit staff nurse - Shorter, Melanie (2008)
Aims - To explore the grief experiences of the AICU staff nurse, their perceived coping mechanism when a patient dies, and the perceived effects on the AICU staff nurse.